The legislative role of DPRD in Regional Regulation Formation: A Study of Simalungun Regency (2019–2024) - Jarima Gita Susilo Ginting; Faisal Andri Mahrawa (Privietlab, 2026)
In the case of Indonesia's decentralized governance structure, the Regional House of Representatives, or the Dewan Perwakilan Rakyat Daerah (DPRD) has three principal roles, which include legislation, budgetary control, and oversight. Out of these roles, the legislative function tends to hold the most prominence as it is through this function that the DPRD, in conjunction with the other branch of government—the regional head (executive)—drafts and adopts regional bylaws (Peraturan Daerah or Perda) which serve as the legal basis for the governance and development of the region. The Simalungun Regency which is also an autonomous locality in North Sumatra, has its own peculiarities in the way it develops this Perda. One of the reasons making the 2019–2024 DPRD period interesting is the recurrence of the backlog of regional regulation draft papers (Ranperda) in this period. The study relies on the use of descriptive qualitative approaches that live data collection to arrive at the details pertaining to the phenomena that is the subject of the inquiry. This research used interviews as its primary data collection tool in the field with respect to the research participants. The findings suggest that the Simalungun Regency DPRD’s 2019–2024 legislative function is yet to be fully institutionalized, as there were a number of constraints including the limited availability of human resources. The DPRD’s legislative ‘right of initiative’ was also less pronounced.